High-Intensity Interval Training and Sprint-Interval Training in National-Level Rowers - Turner, Kirstie Jodie; Pyne, David Bruce; Périard, Julien D.; Rice, Anthony John (Frontiers in Physiology, 2021)
Purpose: The effects of two different high-intensity training methods on 2000 m rowing ergometer performance were examined in a feasibility study of 24 national-level rowers aged 18-27 y (17 male, 2000 m ergometer time trial 6:21.7 ± 0:14.6 (min:sec) and 7 female, 2000 m ergometer 7:20.3 ± 0:12.1. Habitual training for all participants was 12-16 hours per week). Methods: Sixteen high-intensity ergometer sessions were completed across two 3-week periods. Participants were allocated into two groups according to baseline 2000 m time. HIIT-SIT completed 8 high-intensity interval sessions (HIIT: 8 x 2.5 min intervals; 95% of 2000 m wattage) followed by 8 sprint-interval sessions (SIT: 3 sets of 7 x 30 s intervals; maximum effort). SIT-HIIT completed 8 SIT sessions followed by 8 HIIT sessions. Both a 2000 m time trial and a progressive incremental test finishing with 4 min ‘all-out’ performance were completed before and after each 3-week phase. Results: Both groups showed similar improvements in 2000 m time and 4 min ‘all-out’ distance after the first 3 weeks (2000m time: HIIT-SIT: -2.0 ± 0.6%, mean ± 90% CL, p=0.01; SIT-HIIT: -1.5 ± 0.3%, p=0.01) with no significant difference between groups. HIIT-SIT demonstrated the greatest improvements in submaximal HR during the progressive incremental test with 8 sessions of HIIT showing a greater reduction in submaximal HR than 8 sessions of SIT. The net improvement of 16 high-intensity sessions on 2000 m time was -2.5% for HIIT-SIT (-10.6 ± 3.9 s, p=0.01) and -2.2% for SIT-HIIT (-9.0 ± 5.7 s, p=0.01) and for 4 min ‘all-out’ performance was 3.1% for HIIT-SIT (36 ± 25 m, p=0.01) and 2.8% for SIT-HIIT (33 ± 27 m, p=0.01). Conclusion: Eight sessions of high-intensity training can improve 2000 m ergometer rowing performance in national-level rowers, with a further 8 sessions producing minimal additional improvement. The method of high-intensity training appears less important than the dose.